2008
DOI: 10.1088/0031-9155/53/18/001
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of longitudinal breathing motion randomness for tomotherapy delivery

Abstract: The purpose of this study is to explain the unplanned longitudinal dose modulations that appear in helical tomotherapy (HT) dose distributions in the presence of irregular patient breathing. This explanation is developed by the use of longitudinal (1D) simulations of mock and surrogate data and tested with a fully 4D HT delivered plan. The 1D simulations use a typical mock breathing function which allows for more flexibility to adjust various parameters. These simplified simulations are then made more realisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 21 publications
(51 reference statements)
2
44
0
Order By: Relevance
“…different from 5 s) during the whole treatment, by selecting an appropriate but still comfortable breathing period. Fortunately, such aliasing is not relevant for the helical treatment delivery, the latter being rather insensitive to beam and tumor motion interplay effects [29][30][31]. Secondly, the influence of surrounding tissues or bones in the registration procedure may result in erroneous tumor positioning.…”
Section: Discussionmentioning
confidence: 99%
“…different from 5 s) during the whole treatment, by selecting an appropriate but still comfortable breathing period. Fortunately, such aliasing is not relevant for the helical treatment delivery, the latter being rather insensitive to beam and tumor motion interplay effects [29][30][31]. Secondly, the influence of surrounding tissues or bones in the registration procedure may result in erroneous tumor positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Several other authors have found no significant dose difference using sinusoidal waveforms. ( 9 , 10 ) Chaudhari et al ( 14 ) have observed more significant differences using real patient rather than sinusoidal breathing patterns between dose distributions for treatments to static versus moving targets. They have observed larger errors due to motion in real patients only for cases of the breathing pattern with a drift toward inhalation (motion drifting inferiorly).…”
Section: Discussionmentioning
confidence: 99%
“…( 7 , 11 13 ) Other studies have found that there are significant effects, even with sinusoidal motion ( 6 ) or with only real patient breathing patterns. ( 9 , 14 ) …”
Section: Introductionmentioning
confidence: 99%
“…In this case, the results should be an approach to show the effects of a vertical and lateral motion of a typical patient with regular shallow breathing patterns on the surface dose. The dose effects of longitudinal breathing were not measured, as actual research found only small dose deviations for the typical breathing motion patterns [8]. The results of the patients showed a homogeneous dose distribution for both HT and 3D-CRT, with discrete advantages for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…In each setup, a comparison between surface doses displayed in the planning software and measured doses was done, although other studies found, that the validity of the plan doses is limited near the air-to-skin transition [13]. Since the latest research has shown that the longitudinal breathing motion-induced dose error in the treatment of breast cancer with HT is relatively insignificant for typical breathing patterns, this study investigates the possible dose effects of motion in a transverse plane in the radiation field [8].…”
Section: Introductionmentioning
confidence: 99%